Frances Policy in Syria between the years 1928-1936 - موسى عصام; محمد الحسين; كنده كنهير (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The research talks about the French policy in Syria after since the great Syrian Revolution, until the signing of the Franco- Syrian Treaty, and that no matter how different The names, personalities, and endeavors of the French high delegates are in studying the Syrian situation, and the political developments that took place, The French policy was the same, it is the affirmation of the occupation and the plundering of the Syrians wealth, and follow the policy of killing, exile, destruction, imprisoning and torturing Syrian patriots, To submit to French conditions, The French policy in Syria was clear and its justifications were ready befor other foreign countries and the league of Nations, Therefore, this policy did not receive from the Syrians anything but a call for unity, independence and resistance to the French occupation by all means until they reach their rights.